2004
DOI: 10.1508/cytologia.69.101
|View full text |Cite
|
Sign up to set email alerts
|

DNA Content of Individual Mitochondrial Nucleoids Varies Depending on the Culture Conditions of the Yeast Saccharomyces cerevisiae

Abstract: SummaryThe DNA content of individual mitochondrial nucleoids (mt-nucleoids) in the stationary-phase cells of the yeast Saccharomyces cerevisiae was quantitatively measured by a combination of DAPI-staining and use of a video-intensified microscope photon counting system (VIMPCS). The mt-nucleoids in the cells which were grown aerobically in AN medium contained, on average, 1.5 mitochondrial DNA (mtDNA) molecules per mt-nucleoid, and the mt-nucleoids that were isolated from these cells contained 1.1 mtDNA molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 17 publications
3
15
0
Order By: Relevance
“…For example, aerobically grown diploid cells of the yeast Saccharomyces cerevisiae contain, on average, 100 molecules of 85-kbp mtDNA. With a distance of 0.34 nm between base pairs in DNA, the total length of mtDNA reaches almost 3 mm per cell, while the diameter of the cell does not exceed 3 to 4 m. Analogously to its nuclear counterpart, mtDNA must be packaged into condensed nucleoprotein structures termed mitochondrial nucleoids (mt-nucleoids) (1)(2)(3)(4)(5)(6). The size of mt-nucleoids in S. cerevisiae ranges from 0.2 to 0.9 m, meaning that mtDNA in yeasts undergoes compaction of roughly 3 orders of magnitude.…”
mentioning
confidence: 99%
“…For example, aerobically grown diploid cells of the yeast Saccharomyces cerevisiae contain, on average, 100 molecules of 85-kbp mtDNA. With a distance of 0.34 nm between base pairs in DNA, the total length of mtDNA reaches almost 3 mm per cell, while the diameter of the cell does not exceed 3 to 4 m. Analogously to its nuclear counterpart, mtDNA must be packaged into condensed nucleoprotein structures termed mitochondrial nucleoids (mt-nucleoids) (1)(2)(3)(4)(5)(6). The size of mt-nucleoids in S. cerevisiae ranges from 0.2 to 0.9 m, meaning that mtDNA in yeasts undergoes compaction of roughly 3 orders of magnitude.…”
mentioning
confidence: 99%
“…Mitochondrial nucleoids contain more than one equivalent of mtDNA per nucleoid (102,147). MacAlpine et al (90) found that the distribution of mtDNA in the nucleoids was under the control of the general amino acid control circuit.…”
Section: Acetohydroxyacid Reductoisomerase and Mtdnamentioning
confidence: 99%
“…Subsequently, we isolated mt-nucleoids from the spheroplasts of yeast cells, maintaining their structure in vivo, and showed that specific DNA-binding proteins compactly packaged 3-4 copies of mtDNA into chromatin-like structures (Miyakawa et al 1987(Miyakawa et al , 1995(Miyakawa et al , 2010. In addition, we demonstrated that a single mt-nucleoid in rho + cells, which are grown anaerobically, contains ∼20 copies of mtDNA, but a single mt-nucleoid in cells grown aerobically in the same medium contains only 1-2 copies of mtDNA (Miyakawa et al 2004). These results show that the size and number of mt-nucleoids per cell are not constant but rather dynamically change depending on culture conditions or the stage of life cycle of the yeast cells, as well as the copy number of mtDNA per cell.…”
Section: Introductionmentioning
confidence: 55%